Influence of Energy Intake on Egg Production and Weight in Indigenous Chickens of Kenya - Kingori , A.M.; Wachira, A.M.; Tuitoek, J.K. (International Journal of Poultry Science, 2014)
Indigenous chickens are widespread within the rural areas of Kenya where they contribute more than 50% of the domestic egg requirement. Although they contribute a significant proportion of egg requirements, the productivity is low. Poor nutrition is one of the reasons for the low productivity of indigenous chickens. They depend primarily on the scavenging feed resource base for nutrients. Scavenging is an uncertain method of feeding because the scavenged rations may be inadequate in nutrient supply. Productivity of indigenous chickens can be achieved through improved nutrition by supplementation to supply the deficient nutrients. The energy requirements of growing indigenous chickens have been determined and the energy intakes of the free-ranging chickens have been estimated. However, the energy requirements of indigenous chicken hens in Kenya have not been determined, hence the need to determine the requirements. An on-station feeding trial was conducted to determine the influence of energy intake on egg production, egg and hen weight. Two summit diets were formulated containing 18 and 24% Crude Protein (CP). They were blended in various ratios (diet 2 = 67% of diet 1 and 33% of diet 4; diet 3 = 33% of diet 1 and 67% of diet 4) to obtain two other diets containing 17 and 22% CP. The diets were randomly allocated to 48 indigenous chicken hens 42 weeks of age. Each diet was replicated 4 times and 3 hens were housed per cage. The diets were offered to the hens such that they had similar CP, vitamin and mineral intake but varying energy intake. Egg production, egg and hen weights were measured over an eight-week period. Egg production increased (p < 0.05) with increasing energy intake from (813-1034 kJ/d). Egg weight was similar (p>0.05) for energy intake between 813-1185 kJ. Final hen weight was similar (p>0.05) for energy intake between 813-874 kJ and increased from an intake of 1034 kJ. From the results, it is concluded that the daily metabolizable energy requirement for a laying indigenous chicken hen given adequate proteins and other nutrients is 1185 kJ.